Comparative Analysis of Company Profitability in the Financial Sector Before and During the Covid-19 Pandemic - Elfaz, Maulanisa Arifa; Hayya, Najwa Khairina; Aulia, I'anatul; Jufri, Achmad; Darmawan, Darmawan (Journal of Economics and Public Health, 2022)
This study aims to find out how the level of profitability of a company by using the ratio of ROA (Return on Assets), ROE (Return on Equity), and NPM (Net Profit Margin) in the financial sector. This study uses a quantitative descriptive research method. The type of data in this study is secondary data taken from the financial statements of PT BFI Finance Indonesia Tbk. and PT Bank Pan Indonesia Tbk. over an eleven year period. The data collection technique used for recording is data obtained from the financial statements of PT. Bank Pan Indonesia Tbk. and PT BFI Finance Indonesia Tbk. in the form of a balance sheet and income statement for 2011-2021. The results of the research based on the analysis of the profitability of the two companies in the financial sector show that ROA fluctuated from 2011 - 2021. The results of the calculations show that the ratio of profitability of NPM and ROA of PT. BFI Finance Indonesia Tbk. better than PT. Bank Pan Indonesia Tbk, meaning PT. BFI Finance Indonesia Tbk., is more effective and efficient in managing costs in the sales process, thus obtaining a higher net profit from sales. While the ROE ratio of PT. Bank Pan Indonesia Tbk. better than PT. BFI Finance Indonesia Tbk. NPM and ROA profitability ratios at PT. Bank Pan Indonesia Tbk. still under PT. BFI Finance Indonesia Tbk. This shows that the company's performance is not good based on its profitability ratio. It can be concluded that PT BFI Finance Indonesia Tbk is a better company than PT Bank Pan Indonesia Tbk based on the calculation of the probability ratio.